Recycling of mixed plastic waste from electrical and electronic equipment. Added value by compatibilization. (July 2016) - Vazquez, Yamila V.; Barbosa, Silvia E.
Highlights: Mechanical reprocessing of WEEE plastics is proposed. Enhance phase adhesion and add value to new plastic WEEE blend by compatibilization. Plastic WEEE recycling by compatiblization with the addition of a low cost copolymer. Significant improvement in final properties of mixed plastic WEEE blend. Abstract: Plastic waste from electrical and electronic equipment (WEEE) grows up exponentially fast in the last two decades. Either consumption increase of technological products, like cellphones or computers, or the short lifetime of this products contributes to this rise generating an accumulation of specific plastic materials such ABS (Acrylonitrile-Butadiene-Styrene), HIPS (High impact Polystyrene), PC (Polycarbonate), among others. All of they can be recycled by themselves. However, to separate them by type is neither easy nor economically viable, then an alternative is recycling them together as a blend. Taking into account that could be a deterioration in final properties, to enhance phase adhesion and add value to a new plastic WEEE blend a compatibilization is needed. In this work, a systematical study of different compatibilizers for blends of HIPS and ABS from WEEE was performed. A screening analysis was carried out by adding two different compatibilizer concentration (2 wt% and 20 wt%) on a HIPS/ABS physical blend 80/20 proportion from plastic e-waste. Three copolymers were selected as possible compatibilizers by their possible affinity with initial plastic WEEE. A complete characterization of each WEEE was performed and compatibilization efficiency was evaluated by comparing either mechanical or morphological blends aspects. Considering blends analyzed in this work, the best performance was achieved by using 2% of styrene-acrylonitrile rubber, obtaining a compatibilized blend with double ultimate strength and modulus respect to the physical blend, and also improve mechanical properties of initial WEEE plastics. The proposed way is a promise route to improve benefit of e-scrap with sustainable, low costs and easy handling process. Consequently, social recycling interest will be encouraged by both ecological and economical points of view.